2013
DOI: 10.1021/cm400945h
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole/Sulfone Hybrid D-π-A-Structured Bipolar Fluorophores for High-Efficiency Blue-Violet Electroluminescence

Abstract: Based on a D-π-A structural strategy incorporating carbazole as a mild electron-donor and sulfone as an electron-acceptor with a π-conjugation-breaking feature, two novel blue-violet emitting materials (CzS1 and CzS2) were successfully designed and synthesized. The two compounds exhibit high-efficiency fluorescent emissions of intramolecular charge-transfer transition type, with impressively high quantum yields in both solution and film states. CIE y below 0.06 and excellent current/power efficiencies up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
97
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(107 citation statements)
references
References 65 publications
3
97
0
1
Order By: Relevance
“…Solutioneprocessed and nonedoped OLEDs have attracted more and more attention [30,31]. Very recently, Lee et al reported solutioneprocessed OLEDs using TADF materials as emitters [9].…”
Section: Introductionmentioning
confidence: 99%
“…Solutioneprocessed and nonedoped OLEDs have attracted more and more attention [30,31]. Very recently, Lee et al reported solutioneprocessed OLEDs using TADF materials as emitters [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among three basic colors of blue, green, and red for full-color displays, development of high-efficiency blue-light-emitting materials is important. Because the short-wavelength emission can serve as an excitation source for emissions over the whole visible range [2]. Since the first report on blue PLEDs device which was fabricated with poly(p-phenylene) (PPP) in 1992 [3], a large number of materials for blue-light-emitting have been developed [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Blue light-emitting materials are of great significance for their unique applications in flat-panel displays and high-density information storage. Especially in full-color displays, the short-wavelength emission can serve as an excitation source for emission over the whole visible range [10]. Therefore, development of high-efficiency blue emitting materials is important.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the fluorene sequences were selected as D for the reason of good thermal and electrochemical stability, high fluorescence yield and facile chemical functionalization [13,14], while 1,2,4,5-tetrazine (tetrAz) and 1,3,5-triazine (triAz) were chosen as A for their electron deficiency [12]. …”
Section: Introductionmentioning
confidence: 99%